A global view of the phase transitions of SnO2 in rechargeable batteries based on results of high throughput calculations. Issue 38 (14th October 2015) - Cheng, Yingchun; Nie, Anmin; Gan, Li-Yong; Zhang, Qingyun; Schwingenschlögl, Udo
<x xml:space="preserve">Abstract</x> The Materials Project database of high throughput first principles calculations is used to investigate the phase transitions of SnO2 during ion intercalation and extraction.